2002
DOI: 10.1042/0264-6021:3630745
|View full text |Cite
|
Sign up to set email alerts
|

Threonine-124 and phenylalanine-448 in Citrobacter freundii tyrosine phenol-lyase are necessary for activity with l-tyrosine

Abstract: Thr-124 and Phe-448 are located in the active site of Citrobacter freundii tyrosine phenol-lyase (TPL) near the phenol ring of a bound substrate analogue, 3-(4'-hydroxyphenyl)propionic acid [Sundararaju, Antson, Phillips, Demidkina, Barbolina, Gollnick, Dodson and Wilson (1997) Biochemistry 36, 6502-6510]. Thr-124 is replaced by Asp and Phe-448 is replaced by His in the crystal structure of a structurally similar enzyme, Proteus vulgaris tryptophan indole-lyase, which has 50% identical residues. Hence, Thr-124… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 32 publications
6
37
0
Order By: Relevance
“…We postulate that these residues are important for determining the specificity towards the physiological substrate. A catalytic role has been previously established only for two of these residues, Thr124 and Phe448 (45). Finally, we note that a hydrogen bonding network connecting the ε-amino group of Lys257 and the phenolic hydroxyl of Tyr71 (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…We postulate that these residues are important for determining the specificity towards the physiological substrate. A catalytic role has been previously established only for two of these residues, Thr124 and Phe448 (45). Finally, we note that a hydrogen bonding network connecting the ε-amino group of Lys257 and the phenolic hydroxyl of Tyr71 (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of this substrate strain to catalysis can be estimated by the effects of mutagenesis of Thr-124 and Arg-381 on k cat /K m for elimination of phenol from L-tyrosine, since the short strong hydrogen bonds formed in the strained intermediate are needed to overcome the higher energy of the bent structure. T124A TPL has k cat /K m reduced by about 10 3 , and R381A TPL has k cat /K m reduced by about 10 5 [27]. Thus, the ground state strain can be estimated to contribute at least 10 8 to catalysis by TPL.…”
Section: Crystallography Of Substrate and Inhibitor Complexes Of Til mentioning
confidence: 95%
“…The active site tyrosine is essential for activity, as Y71F mutant TPL and Y74F mutant TIL show no detectable elimination activity (i.e., <10 À5 that of wildtype) with their physiological substrates [22,25,26], although both have significant activity with SOPC and other non-physiological substrates with good leaving groups. Although TIL and TPL show strict substrate specificity for their physiological substrates, mutation of Thr-124, Arg-381 and Phe-448 in TPL to the corresponding residues of TIL, aspartate, isoleucine and histidine, respectively, resulted in loss of TPL activity, retention of SOPC elimination activity, but no detectable TIL activity [21,27].…”
Section: Structure Of Til and Tplmentioning
confidence: 97%
“…The molecular basis of this behavior has been investigated by site‐directed mutagenesis (Phillips et al 2003). The transition between open (inactive) and closed (active) states of these enzymes accompanies substrate binding and the catalytic cycle (Demidkina et al 2002; Phillips et al 2003), as also observed in other PLP‐dependent enzymes belonging to the α‐ (Schirch et al 1991; McPhalen et al 1992) and β‐functional family (Schneider et al 1998; Burkhard et al 1999).…”
mentioning
confidence: 79%